RESPIRATION DETECTION TOOLS IN HUMAN BASED ARDUINO UNO - Bastari, Winarno Fadjar; Amanullah, Mohamad Habib (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2020)
The vital capacity value of the lungs is very influential with the health of the human lungs because with the results the value of the vital capacity of the human lung can be diagnosed as normal or abnormal of the lungs. This study aims to make a means of detecting respiration gas flow rates in humans using an arduino uno-based YF-S201 flow sensor. From the results of data analysis of respiratory gas flow in adult male breathing with ages (20 years - 30 years), (30 years - 35 years), (35 years - 45 years) and (45 years - 50 years) as many as 15 users. there is an error of 3.86%, the value is generated from comparing the output of the equipment made by researchers with other tools of the brand Spirolab with as many as 15 users of different height and age. From 15 different users there are 2 users with abnormal lung conditions and 13 other users with normal lung conditions. The result of this error occurred because of the 15 users who were less relaxed when exhaling and breathing.